The Impact of Globalization, Inequality, and Financial Sector Policies During the Pandemic in Indonesia - Prasetyowati, Riris Aishah (Jurnal Ekonomi Indonesia, 2021)
This study aims to examine the effects of economic globalization, income inequality, and financial sector policies using Indonesian macroeconomic variables. This study uses monthly time series data from 2010 to March 2021, when the Covid19 pandemic occurred and cross section data on 12 macroeconomic variables. The test uses a simultaneous equation with the 2SLS and AB-GMM methods to perform a regression test on the sample. The results show that there is evidence that 10 macroeconomic variables statistically predict Indonesia’s financial sector policies significantly. Second, by using the variables that have been determined previously in the equations shown on the endogenous variables, it found that the level of inequality and financial sector policies does not influence that economic globalization. Similarly, financial sector policies not affected by the level of inequality. On the other hand, economic globalization affects financial sector policies negatively and significantly. Economic globalization also affects the level of inequality negatively andsignificantly. Meanwhile, financial sector policies have a positive and significant impact on the level of inequality. This means that even though there is a pandemic during the observation period, financial sector policies will continue to run according to circumstances and tend to be repressed. This is because in the face of globalization and income inequality in the midst of the pandemic, there has been a liberalization of the government through repressive financial sector policies.